2022
DOI: 10.1038/s41598-022-07251-y
|View full text |Cite
|
Sign up to set email alerts
|

Significance of induced hybridized metallic and non-metallic nanoparticles in single-phase nano liquid flow between permeable disks by analyzing shape factor

Abstract: The current communication is designed by keeping in the mind high heat transfer capabilities of nanoliquids with the dispersion of diversified-natured nanoparticles in poorly conducting base liquids. Here, an amalgamation of metallic (Cu) and hybridization of metallic and non-metallic oxide (Cu-TiO2) nanoparticles to uplift thermophysical attributes of water is deliberated. The magnetically affected flow between rotating disks under the impact and permeability aspect is assumed. Empirical relations for effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Cummins et al 17 elaborated flow past permeable disks at low Reynolds numbers. Bilal et al 18 examined the shape factor effect on hybrid nanofluid between permeable disks using a single-phase flow model. Bashir et al 19 analyzed thermophoresis phenomena between rotating disks under the thermal radiation effect.…”
Section: Introductionmentioning
confidence: 99%
“…Cummins et al 17 elaborated flow past permeable disks at low Reynolds numbers. Bilal et al 18 examined the shape factor effect on hybrid nanofluid between permeable disks using a single-phase flow model. Bashir et al 19 analyzed thermophoresis phenomena between rotating disks under the thermal radiation effect.…”
Section: Introductionmentioning
confidence: 99%
“…The solutions' antifreeze temperature has been set at −20°C, which allows for a fixed primary refrigerant reduction. Using traditional solution-based nanofluids can improve heat transmission even more [5,6]. Recent numerical and experimental investigations have demonstrated that the use of nanofluids as secondary working fluids-coolant on the condenser side and secondary refrigerant on the evaporator side-could improve the heat transfer properties and performance of the refrigeration [7].…”
Section: Introductionmentioning
confidence: 99%
“…2 The amalgamation of NPs with the underlying working fluid has been demonstrated as a potent solution for augmenting TC, leading to improved HT. 3 Numerous articles have surfaced in recent times on metallic, nonmetallic, and quasi-metallic NPs, 4 and the research in this realm is a continuous process. NFs were previously produced using a singular type of NP.…”
Section: Introductionmentioning
confidence: 99%